Strategic technology alliance in manufacturing firms: a conceptual paper - Jabar, Juhaini; Soosay, Claudine (2008)
As organisations deal with dynamic and competitive business environments, many of them face impending issues and challenges in keeping up with technology advancements. Apparently, a number of firms have realised the benefit of forming strategic technology alliances (STAs) with other firms. However, there is little empirical research conducted on this growing practice. This research intends to investigate the drivers of STAs; and if success factors of STAs enable the effective performance of firms. Based on a critical review of the literature, this study aims to integrate five theories that are prominently used in the study of alliances, technology and innovation to form a conceptual framework for empirical investigation of STAs in Malaysian and Australian manufacturing firms. The findings from this study at a later stage will provide theoretical and practical implications into the management perspectives and outcomes of STAs that are formed with the focus of technology in the manufacturing industry.